Analysis of economic factors of Iranian professional football - Seyed Bagheri, Seyed Mehdi; Seyed Hosseini, Rasool Norouzi; Saffari, Marjan; Sharifian, Esmail (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The objective of this study was to analyze the economic factors of Iranian professional football. The participants comprised experts specializing in football and sports economics. The purposive sampling method was employed to identify participants for the research. A total of 12 individuals were selected as the statistical sample. Data analysis was conducted using the Analytical Hierarchical Process (AHP). In the paired comparison questionnaire, participants were asked to assess the relative importance of the economy components. ExpertChoice software was utilized to calculate component weights. The findings revealed that it would be recommendable to depoliticize the football administrative and management system and minimize government interference. Additionally, fostering a tax culture and formulating a provincial tax system tailored to the specific characteristics of football is crucial. Moreover, creating a platform for privatization in football would facilitate free competition.